Narratives of participatory governance: Social science and democracy in mark bevirʼs a theory of governance. Issue 3 (1st March 2016) - Ron, Amit
Abstract : Mark Bevirʼs A Theory of Governance proposes a Copernican revolution in the way we understand the role of social science in public administration. Conventional accounts assign social science the role of instructing public administrators how to steer its machinery towards the public interest, based on social scienceʼs alleged ability to explain how people act and what they need. Bevir offers a vision of public administration in which ordinary people take a leading role by engaging in dialogues in which they articulate their needs. In this vision, the role of social science is to facilitate those public dialogues. This essay offers a sympathetic critical evaluation of Bevirʼs exploration of what it means to understand social science as a facilitator.